Dopamine attenuates ethanol-induced neuronal apoptosis by stimulating electrical activity in the developing rat retina - Han Junde; Ge Shuli; Zhang Kan; Zheng Jijian; Dong Jing (Open Medicine)
Prenatal alcohol exposure causes fetal alcohol spectrum disorders (FASD), primarily through alcohol-induced apoptosis. This study explores the link between ethanol-induced neuronal apoptosis and neural network electrical activity in developing rat retinal ganglion cells, and examines dopamine’s protective effects and influence on this activity.